Extension Of Cocoa Fermentation and Drying Techniques In Pussui Village - Ikrar Taruna Taruna Syah; Ihsan Arham; Rahmaniah Rahmaniah (Fakultas Sains Dan Teknologi, Universitas Muhammadiyah Sidenreng Rappang, 2025)
Pussui Village is one of the villages which has a quite large cocoa farm, located in Luyo District, Polewali Mandar Regency. With this high potential yield, proper post-harvest handling is required to produce high-quality dried cocoa beans. Good post-harvest handling practices have not been implemented by farmer groups in Pussui Village. The dried cocoa beans are sold directly to the traders. The intervention that can be carried out is a training program that focuses on proper fermentation and drying techniques by increasing the farmer's capability by developing their skill and knowledge and applying tools to this process. This training was expected to reduce the low quality of the dried cocoa beans which will affects the price of the cocoa beans in Pussui Village. This intervention was realized through an approach involving the provision of teaching materials in the class, practical sessions in fermentation and drying houses, as well as evaluation of post-training through questionnaires given after the training. This activity is part of the Kosabangsa 2023 program. The evaluation results show that this activity can increase participants' knowledge by 40% and 35% in fermentation and drying techniques. Furthermore, for the level of usefulness, farmers rated this activity as very useful by scores of 44% and 47%.